2007
DOI: 10.1254/jphs.fp0070436
|View full text |Cite
|
Sign up to set email alerts
|

Development of Numerous Nerve Fibers in the Epidermis of Hairless Mice With Atopic Dermatitis-Like Pruritic Skin Inflammation

Abstract: Abstract. Itching is the most important symptom in atopic dermatitis because the persistent scratching in response to itching aggravates the disease. However, the etiologic mechanisms of itching in atopic dermatitis remain uncertain. HR-1 hairless mice fed a special diet, HR-AD, develop atopic dermatitis-like symptoms with prolonged scratching episodes. The purpose of this study was to examine whether skin nerve fiber changes were involved in the prolonged scratching seen in this mouse model. On day 56 after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Sensitization of itch-signaling pathways has been proposed as a critical mechanism underlying chronic itch (41,42). In ACD and atopic dermatitis, nerve fiber densities are increased in the epidermis (43,44). Extension of these nerve fibers into the epidermis may contribute to spontaneous itch, aggravating itch responses and sensitization of itch signaling pathways (42).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization of itch-signaling pathways has been proposed as a critical mechanism underlying chronic itch (41,42). In ACD and atopic dermatitis, nerve fiber densities are increased in the epidermis (43,44). Extension of these nerve fibers into the epidermis may contribute to spontaneous itch, aggravating itch responses and sensitization of itch signaling pathways (42).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that nerve fibres were increased in the skin of atopic dermatitis or atopic‐dermatitis‐like pruritic skin inflammation . Thus, inhibition of nerve fibre penetration could be an appropriate strategy for treating skin diseases characterized by pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…In HR-AD diet-fed HR-1 mice, nerve fibers markedly increased in the epidermis (24). The increase in intraepidermal nerve fibers, as well as the skin barrier dysfunction, plays a crucial role in the increased scratching behavior.…”
Section: Effects Of Wasabi Rhizome Extract On Scratching Behaviormentioning
confidence: 97%